Development of The Rifa'iyah Batik E-module Based on Local Wisdom for Increase Ability Cognitive Student in Batik Learning - Marlangen, Retno; Kusumastuti, Adhi; Sutopo, Yeri; Wahyuningsih, Sri Endah (Jurnal Penelitian Pendidikan, 2025)
Batik learning at SMKN 1 Warungasem is using general materials. The learning are not focusing on integrating local riches of Batang Regency such as Rifa'iyah batik and not using interactive media in the learning process. It resulted in students lack of understanding on Rifa'iyah batik, impacted in late regeneration of Rifa'iyah batik workers. This study aims to develop a Rifa'iyah batik e-module based on local wisdom to improve students' cognitive abilities. The method used is the Research and Development (R&D) ADDIE model through the stages of analysis, design, development, implementation, and evaluation. The product was validated by 3 media experts and 3 material experts; the effectiveness was tested through pre-tests and post-tests on the control class and the experimental class of 70 students. The results showed that the e-module was declared feasible by media experts with an average score of 3.99 and very feasible by material experts with a score of 4.46. The effectiveness test showed an N Gain score of 76% in the experimental class, higher than the control class, and the independent t- test showed a significant difference in learning outcomes after treatment. It can be concluded that the Rifa'iyah batik e-module is valid, feasible, and effective for improving students' cognitive abilities in batik learning.